Respuesta :

Answer:

3) a. f(-4) = 2

   b. f(0) = 0

   c. f(3) = -1.5

   d. f(-5) = 0

   e. x = -4

    f. x= 0

4) a. f(-1) = 1

   b. f(3) = -1

   c. 1

   d. -5

5) f(6) = 2

   f(2) = 4

   f(0) = 7

   f(5) = 1.5

    x=4

Answer:

see below

answers as required.

3)

a. [tex]f[/tex](-4) = 2

b. [tex]f[/tex](0) = 0

c. [tex]f[/tex](3) = -1.5

d. [tex]f[/tex](-5) = 0

e. x = -4

f. x= 0

4)

a. [tex]f[/tex](-1) = 1

b. [tex]f[/tex](3) = -1

c. 1

d. -5

5)

[tex]f[/tex](6) = 2

[tex]f[/tex]f(2) = 4

[tex]f[/tex](0) = 7

(5) = 1.5

x=4